2010
DOI: 10.1371/journal.ppat.1000837
|View full text |Cite
|
Sign up to set email alerts
|

Prion Shedding from Olfactory Neurons into Nasal Secretions

Abstract: This study investigated the role of prion infection of the olfactory mucosa in the shedding of prion infectivity into nasal secretions. Prion infection with the HY strain of the transmissible mink encephalopathy (TME) agent resulted in a prominent infection of the olfactory bulb and the olfactory sensory epithelium including the olfactory receptor neurons (ORNs) and vomeronasal receptor neurons (VRNs), whose axons comprise the two olfactory cranial nerves. A distinct glycoform of the disease-specific isoform o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 53 publications
(88 reference statements)
5
68
0
4
Order By: Relevance
“…68 These data support the secretion of the prion agent into the lumen of the nasal airway. However, given that the effects of route of inoculation, host species and TSE strain on PrP Sc location within the nasal tissues is yet to be defined, prion shedding via nasal secretion within natural prion infections requires confirmation.…”
Section: Secretion Of Prions Within Milkmentioning
confidence: 56%
“…68 These data support the secretion of the prion agent into the lumen of the nasal airway. However, given that the effects of route of inoculation, host species and TSE strain on PrP Sc location within the nasal tissues is yet to be defined, prion shedding via nasal secretion within natural prion infections requires confirmation.…”
Section: Secretion Of Prions Within Milkmentioning
confidence: 56%
“…Em ambos os animais, estas lesões, apesar de mais evidentes no tronco encefálico ao nível do óbex, foram observadas também no mesencéfalo, ponte, medula oblonga, cornos laterais e ventrais da medula espinhal, concordando com as descrições de Summers et al (1995), Driemeier (2007), Maxie & Youssef (2007) Hoinville (1996), este teste é de grande utilidade para o diagnóstico da doença em animais recém-infectados, em fase de incubação ou com sinais iniciais da doença, quando as alterações histopatológicas ainda podem estar ausentes ou serem incipientes, com possibilidade de diagnóstico falso negativo na histopatologia. Neste caso, segundo Haritani et al (1994) (Thomzig et al 2007), leite (Konold et al 2008, Lacroux et al 2008, Maddison et al 2009, Ligios et al 2011, fezes (Tamgüney 2009;,Terry et al 2011), urina (Murayama et al 2007, Gregori et al 2008, Rubenstein et al 2011, saliva (Vascellari et al 2007, sangue (Murayama et al 2007, Edwards et al 2010 e secreções nasais (Bessen et al 2010). A placenta, segundo é via por onde o PrP sc é mais intensamente eliminado, mas as demais fontes não devem ser negligenciadas, ao se estabelecer medidas de controle sanitário da doença.…”
Section: Resultsunclassified
“…No segundo surto, com base na literatura recente, o comprometimento de somente um macho não é suϐiciente para se concluir pela impossibilidade de disseminação da doença, uma vez que autores como Murayamaet al (2007), Thomzig et al (2007), Vascellari et al (2007), Gregori et al (2008), Tamgüney (2009), Bessen et al (2010, , Rubenstein et al (2011) e Terry et al (2011, aϐirmam que o ovino infectado com PrP sc de scrapie clássi-ca pode excretar o agente por diversas vias tais como pele, fezes, urina, saliva e secreções nasais. Neste caso, infere-se que o macho infectado também adquira importância na disseminação do PrP sc e no controle da doença em um plantel.…”
Section: Discussionunclassified
“…For this reason, major efforts have been undertaken to identify peripheral lymphoid tissues for antemortem collection and diagnosis which may exhibit sensitivities comparable to those of the brainstem/RLN, including third-eyelid, tonsil, and recto-anal mucosa-associated lymphoid tissue (RAMALT) samples (27,(32)(33)(34)(35)(36)(37). Previous studies have additionally demonstrated high levels of PrP res in olfactory epithelium and nasal secretions in several prion diseases (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48), though this prospect has not been assessed with CWD. Both RA-MALT biopsy specimens and nasal brush samples collected from the olfactory epithelium are easily and efficiently collected and processed, making these tissues promising additions in the area of antemortem detection of prion diseases and the samples of choice for our study.…”
mentioning
confidence: 99%